Industrial ecology, climate adaptation, and financial risk. (20th August 2019) - Busch, Timo
Abstract: Climate adaptation has become an important topic for risk management in companies. This article investigates the usefulness of Industrial Ecology tools and concepts in this context. The conclusion is that the established tools and concepts were not designed with the purpose of assisting managers in the climate adaptation and related financial risk context. Nevertheless, the tools and concepts offer plenty of aspects and features that are helpful for the assessment and management of climate risks. The tools primarily provide guidance for the managerial decision‐making process, notably in terms of data handling. The concepts can be used as a starting point for developing new climate risk management frameworks.